Multiple Adenomatous Duodenal Polyposis. (31st March 2013) - Zádorová, Zdena; Hajer, Jan; Mandys, Václav
Abstract : Multiple duodenal polyps are a relatively rare finding, usually co-occurrent with familial adenomatous polyposis (FAP).We report a patient with multiple duodenal adenomas and a negative examination for FAP: multiple flat polyps were detected endoscopically in a 37-year-old male patient, extending from the apex of the bulb to the end of the descending part of the duodenum. In terms of histology, they were tubular adenomas with moderate dysplasia. Colonoscopy and enteroclysis were normal. Both push and capsule enteroscopy only showed multiple polyps in the area of the descending duodenum. DNA analysis of the APC gene was as follows: DGGE, exon 1–15, deletion at codons 1309 and 1061 by means of PCR for attenuated APC were negative. Afterwards we screened the patient for germline MYH mutations using the denaturing high-performance liquid chromatography (DHPLC) in combination with sequencing. No novel pathogenic mutation has been identified. Large polyps were removed by means of endoscopic polypectomy and mucosectomy, while small polyps were removed by means of argon plasma coagulation.We conduct yearly checkups, removing only sporadic polyps. The rare finding of duodenal polyposis not co-occurrent with FAP proves that multiple adenomas in the digestive tube need not necessarily co-occur with FAP.